A heuristic approach for scheduling activities with 'OR'-precedence constraints at an underground mine. Issue 10 (25th November 2020) - Nancel-Penard, Pierre; Morales, Nelson; Rojas, Valentina; González, Tomás
ABSTRACT: Medium-term development planning of underground mines requires scheduling multiple activities to comply with long-term milestones, and to obtain a time span as short as possible. However, the planning must also respect the availability of construction resources and precedence constraints, which in our case can be disjunctive, that is with more than one alternative predecessor. In this paper, we present an optimisation model to find the schedule of minimum length, satisfying all the constraints mentioned. We develop a heuristic approach to solve it and show that it can be used to produce feasible development plans in a real mine.